Unraveling the Catalytic Synergy between Ti3+ and Al3+ Sites on a Chlorinated Al2O3: A Tandem Approach to Branched Polyethylene. (21st July 2016) - Piovano, Alessandro; Thushara, K. S.; Morra, Elena; Chiesa, Mario; Groppo, Elena
Abstract: An original step‐by‐step approach to synthesize and characterize a bifunctional heterogeneous catalyst consisting of isolated Ti 3+ centers and strong Lewis acid Al 3+ sites on the surface of a chlorinated alumina has been devised. A wide range of physicochemical and spectroscopic techniques were employed to demonstrate that the two sites, in close proximity, act in a concerted fashion to synergistically boost the conversion of ethylene into branched polyethylene, using ethylene as the only feed and without any activator. The coordinatively unsaturated Al 3+ ions promote ethylene oligomerization through a carbocationic mechanism and activate the Ti 3+ sites for the traditional ethylene coordination polymerization.